Estimated ages of sediment core SF-07 obtained along the coastal plain of Babitonga Bay-Santa Catarina-Brazil - Marcelo Cancela Lisboa Cohen; Neuza Fontes; Érika do Socorro Ferreira Rodrigues; Luiz C R Pessenda; Marlon França; Ed Garret; Junghyung Ryu (PANGAEA, 2025)
The cores were collected during the winter season in August 2017 using Russian-type sampling equipment. Sediment cores were obtained from tidal flats colonized by mangroves (SF-07, SF-08), herbs (SF-09), and ombrophilous forest (SF-10).
In: Cohen, MCL et al. (2025): Topographic, vegetation, radiocarbon and stratigraphic data from Babitonga Bay-Santa Catarina-Brazil [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.985002